Microleakage Assessment of Single Cone Gutta Percha Obturation Technique Using Different Types of Sealers - Elatrash, Anas; Alawjali, Samia; Bubteina, Nagat (AlQalam Journal of Medical and Applied Sciences, 2024)
This study was carried out to compare the coronal and apical seal of canals obturated with single cone technique using different types of epoxy resin root canal sealers. A total of sixty extracted human upper molars with fully formed and sound palatal roots were used in this study. The crown of each tooth was decoronated at cement-enamel junction and the palatal root canal was prepared using ProTaper gold rotary instruments. Sixty specimens were used and divided into 3 equal groups(n=20) for single cone obturation using two different types of epoxy resin sealers AH26 and vioseal sealers respectively and one control group without sealer. All the specimens were exposed varnish application followed by dye penetration test using 2% methylene blue dye then root sectioning. Samples were evaluated under a stereomicroscope to detect the linear measurement of the dye penetration from the apical constriction. The image transferred to a computer equipped with the image analysis software program where the dye penetration along the filling dentine interface was evaluated. The collected data was statistically analysis by using Graph Pad Instat software for windows. One-way ANOVA was done for compared results followed by Tukey’s pair-wise. The results showed that, the difference in dye penetration microleakage means between groups was statistically significant as revealed by one-way ANOVA test (p < 0.05). Pair-wise Tukey’s post-hoc test showed non-significant (p>0.05) difference between (AH26 and Vioseal sealers) groups. None of the tested root canal sealers could eliminate the dye infiltration or microleakage formation. Single cone gutta-percha combined with AH26 sealer exhibited less microleakage than vioseal sealer although there were no statically significant differences between them.